Preferences of healthcare workers for provider payment systems in The Gambia’s National Health Insurance Scheme - Hassan Njie; Patrick G. C. Ilboudo; Unni Gopinathan; Lumbwe Chola; Knut Reidar Wangen (BMC Health Services Research, 2023)
Abstract Background The Government of The Gambia introduced a national health insurance scheme (NHIS) in 2021 to promote universal health coverage (UHC). Provider payment systems (PPS) are strategic purchasing arrangements that can enhance provider performance, accountability, and efficiency in the NHIS. This study assessed healthcare workers’ (HCWs’) preferences for PPS across major service areas in the NHIS. Methods A facility-based cross-sectional study was conducted using a probability proportionate to size sampling technique to select an appropriate sample size. Health care workers were presented with options for PPS to choose from across major service areas. Descriptive statistics explored HCW socio-demographic and health service characteristics. Multinomial logistic regressions were used to assess the association between these characteristics and choices of PPS. Results The majority of HCW did not have insurance coverage, but more than 60% of them were willing to join and pay for the NHIS. Gender, professional cadre, facility level, and region influenced HCW’s preference for PPS across the major service areas. The preferred PPS varied among HCW depending on the service area, with capitation being the least preferred PPS across all service areas. Conclusion The National Health Insurance Authority (NHIA) needs to consider HCW’s preference for PPS and factors that influence their preferences when choosing various payment systems. Strategic purchasing decisions should consider the incentives these payment systems may create to align incentives to guide provider behaviour towards UHC. The findings of this study can inform policy and decision-makers on the right mix of PPS to spur provider performance and value for money in The Gambia’s NHIS.